Laying the Foundation for Real-World Evidence Studies of Psoriatic Disease in Newfoundland and Labrador - Badaiki, Winifred; Pyper, Evelyn; Lester, Kendra; Skeard, Janelle; Penney, Michelle; Shin, Janey; Fisher, Brenda; Hew, Huong; Gulliver, Susanne; Gulliver, Wayne; Rahman, Proton (International Journal of Population Data Science, 2022)
The Janssen and Newfoundland and Labrador Health Innovation Partnership (JANL-HIP) was established to carry out Real-World Evidence (RWE) projects to generate evidence about disease pathways, healthcare delivery, the effects of clinical interventions. Doing so will support and influence clinical decision-making in Newfoundland and Labrador (NL). This case study describes the foundational elements necessary for a~real-world evidence~generation project in NL and may provide learning for the effective execution of real-world studies in other jurisdictions. It uses an ongoing project in psoriatic disease in NL to illustrate the partnership and the benefits of RWE studies. Ultimately, the JANL-HIP RWE project aims to inform decisions that will drive improvements in health outcomes, system delivery, and policy mutually beneficial to health ecosystem stakeholders.